2015
DOI: 10.1016/j.renene.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Induced flow for ventilation and cooling by a solar chimney

Abstract: a b s t r a c tAn experimental and numerical model of a solar chimney was proposed in order to predict its performance under varying geometrical features in Iraqi environmental conditions. Steady, two dimensional, turbulent flow was developed by natural convection inside an inclined solar chimney. This flow was investigated numerically at inclination angles 15 to 60 , solar heat flux 150e750 W/m 2 and chimney thickness (50, 100 and 150) mm. The experimental study was conducted using a single solar chimney inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(39 citation statements)
references
References 21 publications
(16 reference statements)
0
38
0
1
Order By: Relevance
“…A numerical model of an inclined solar chimney was presented by Imran et al [4]. The model solved two-dimensional (2D) steady-state turbulent flow induced by natural convection, and its functionality was validated with experimental data.…”
Section: Solar Chimneysmentioning
confidence: 99%
“…A numerical model of an inclined solar chimney was presented by Imran et al [4]. The model solved two-dimensional (2D) steady-state turbulent flow induced by natural convection, and its functionality was validated with experimental data.…”
Section: Solar Chimneysmentioning
confidence: 99%
“…In 2015, an experimental and numerical model of a solar chimney was carried out by Imran et al [197] in Iraq for ventilation and cooling a single room. They measured the temperature of the chimney's glass cover, the absorbing wall, and the induced air and analyzed them considering the induced air velocity.…”
Section: Hybrid Solar Chimney Systems and Special Applicationsmentioning
confidence: 99%
“…In [13], the geometrical shape of the solar chimney is studied where it is concluded that after a comprehensive analysis of system output power and efficiency, that the cylindrical chimney would be the best choice among the three basic configurations, whose optimum height to diameter aspect ratio. The work of [14] presents an experimental and numerical model of a solar whereby the maximum air velocity was 0.8 m/s for a radiation intensity of 750 W/m 2 at an air gap of 50 mm thickness. In [15] a novel small scale model of solar chimney was investigated experimentally and numerically where the experimental results show that utilization of intensifiers lead to a maximum velocity of 5.12 m/s.…”
Section: Literature Reviewmentioning
confidence: 99%